The Relationship between Domestic Violence and Maternal- Fetal Attachment - Rabiee 1, Niloofar; Karimi 2, Farzaneh; Abolhassani 3, Moussa; Keramat 4*, Afsane (Shahroud Journal of Medical Sciences, 2019)
Background: Due to the high prevalence of domestic violence among women and more physical and psychological vulnerability during pregnancy, and, consequently, vulnerability to the growing fetus there is an urgent need for accurate identification of these individuals; so the aim of this study was to investigate the relationship between domestic violence and maternal-fetal attachment.Methods: It was a cross-sectional study. 300 women with a gestational age of 20 to 40 weeks were selected randomly and categorically among pregnant women covered by these centers. The data gathering tool was a demographic questionnaire, a domestic violence questionnaire, and maternal-fetal attachment questionnaire.Results: The mean age of the women was 28.32 ± 5.96 years and the mean number of years after the marriage was 7.01 ± 4.22 years and the mean age of the spouse was 31.37 ± 5.93. The mean number of pregnancies was 1.9 ± 1.67. 65.7% of the women experienced mild violence, 19.3% had moderate violence and 15.1% had severe violence. The linear regression of the relationship between the total score of violence with the total score of the attachment of the mothers was significant, along with control of some of their demographic characteristics (P<0.001).Conclusions: Act of physical and psychological domestic violence is effective on maternal attachment to the fetus. Timely screening of the mother for domestic violence can empower and inform the health center staff more effectively in identifying and managing violence against pregnant women and helping to choose alternative behaviors and gaining Communication skills.